Implementación de un sistema web de analítica de datos ambientales para la toma de decisiones en las plantaciones de cacao Sacha Wiwa Guasaganda. - Giler Meza, Anyeleni Yamilex (2023)
The project proposes the development of a web system for the analysis of environmental data for decision-making in cocoa plantations. The system collects information on environmental conditions through strategically located weather stations and sensors. The data will be analyzed by using data analysis techniques to identify patterns and trends. Cocoa producers will be able to access this information through a web platform where they will be able to view the data in a clear and understandable way. With this system, producers will be able to make decisions and optimize plantation management which will contribute to improve the sustainability and profitability of cocoa plantations. The development tools are fundamental elements for the execution of this project because efficient computer programs were selected, such as the PHP programming language, MariaDB database engine, in the same way each system requirement is developed by using an agile methodology, such as the Scrum methodology which allows to implement the software efficiently because it follows certain steps that helps to obtain a system that satisfies the user's needs. In addition, field research was considered for data collection using tools like the survey and interview, as well as bibliographic research for data collection to find the most appropriate tools for the development of the web system and the respective knowledge for the execution of the project. It can be concluded that the implementation of an environmental data analytics web system for decision-making in Sacha Wiwa Guasaganda cocoa plantations is an initiative that improves the ability of farmers to manage crops effectively. By using environmental data and applying smart analytics, the result is a better plantation performance and more sustainable high-quality cocoa production.